PERFORMANCE APPRAISAL SYSTEM AT MUTHRA GLOBAL AT CHENNAI - Dr. G. AMUTHA,K.SUJITH, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The performance appraisal system ideally is an organisation designed programme involving both the organisation and the personnel to improve the capability of both. The elements of performance management include: purpose, content, method, appraiser, frequency, and feedback. The appraisal process involves determining and communicating to an employee how he or she is performing the job and establishing a plan of improvement. The information provided by performance appraisal is useful in three major areas: compensation, placement, and training and development. Appraisal helps to improve performance by identifying the strengths and weaknesses; it helps to identify those with a potential for greater responsibility; and assists in deciding on an equitable compensation system. The methods of performance appraisal include rating scale, critical incident, ranking methods, and management by objectives. Several common errors have been identified in performance appraisal. Leniency occurs when ratings are grouped at the positive 7end instead of being spread throughout the performance scale. The central tendency occurs when all or most employees are ranked in the middle of the rating scale. The halo effect occurs when a manager allows his or her general impression of an employee to influence judgment of each separate item in the performance appraisal.